Range Identification for Nonlinear Parameterizable Paracatadioptric Systems - Nath, Nitendra; Tatlıcıoğlu, Enver; Dawson, Darren M.; Tatlıcıoğlu, Enver (Institute of Electrical and Electronics Engineers Inc., 2009)
In this paper, a new range identification technique for a calibrated paracatadioptric system mounted on a moving platform is developed to recover the range information and the three-dimensional (3D) Euclidean coordinates of a static object feature. The position of the moving platform is assumed to be measurable. To identify the unknown range, first a function of the projected pixel coordinates is related to the unknown 3D Euclidean coordinates of an object feature. This function is nonlinearly parameterized (i.e., the unknown parameters appear nonlinearly in the parameterized model). An adaptive estimator based on a min-max algorithm is then designed to estimate the unknown 3D Euclidean coordinates of an object feature relative to a fixed reference frame which facilitates the identification of range. A Lyapunov-type stability analysis is used to show that the developed estimator provides an estimation of the unknown parameters within a desired precision.
IEEE International Conference on Systems, Man and Cybernetics, SMC 2009; San Antonio, TX; United States; 11 October 2009 through 14 October 2009
Keywords: Three dimensional; Lyapunov methods; Nonlinear parameterization; Paracatadioptric systems; Vision-based estimation